Výroba funkčního prototypu úchytu sedla kola metodou FDM 3D tisku - Zemánek, Patrik (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2016)
Tato bakalářská práce popisuje výrobu prototypu metodou FDM tisku. Cílem této práce bylo se obeznámit s tématem a projít si výrobním procesem prototypu. Na závěr je součást otestována a zhodnocena z ekonomického hlediska.

This bachelor´s thesis describes production of prototype by FDM printing. The aim of this thesis was to acquire knowledge about the topic and undergo the production process of the prototype. Finally the component was tested and evaluated from an economic point of view.
Production of functional prototype of bicycle seat clamp with FDM 3D printing
Keywords: Rapid prototyping; FDM; úchyt; ABS; PC; PLA; Autodesk Inventor; Rapid prototyping; FDM; handle; ABS; PC; PLA; Autodesk Inventor